The Semantic Dimensions of Appeal Discourse in Surat: A Study in the Light of the Speech acts Theory - Ghareeb Qadir, Fakhrya (Al-Adab Journal, 2020)
This study, entitled (The Semantic Dimensions of Appeal Discourse in Surat Yusuf in the Holy Qur’an - A Study in the Light of the Speech acts Theory) aims to uncover the semantic dimensions of the Qur’anic discourse in Surat Yusuf in the Holy Qur’an and monitor its intentions, and to shed light on its direct indications and indirect implications according to The theory of Speech Acts Theory, and the study is composed of three axes as follows:The first axis: the concept of Speech Acts in the Pragmatic lessonThe second axis: the appeal of its appeal, its pillars, achievements and actual forcesThe third axis: The Appeal of the Appeal in Surat Yusuf, its implications and actual achievementsThe study ends its journey with a conclusions and a list of the books and references used in writing.